The apocalypse of Elena Mendoza - Hutchinson, Shaun David (New York, NY : Simon Pulse, 2019)
Elena, the first scientifically confirmed virgin birth, acquires the ability to heal by touch at age sixteen, the same year that people start disappearing in beams of light, causing her to wonder if she is bringing about the Apocalypse.
SHS
In English
Keywords: Healers -- Fiction; Missing persons -- Fiction; End of the world -- Fiction; Miracles -- Fiction; Virgin birth -- Fiction; Science fiction